Growth of lithium hydride thin films from solutions: Towards solution atomic layer deposition of lithiated films - Kundrata, Ivan; Frohlich, Karol; Vanco, Lubomir; Micusik, Matej; Bachmann, Julien (Beilstein Journal of Nanotechnology, 2019)
Lithiated thin films are necessary for the fabrication of novel solid-state batteries, including the electrodes and solid electrolytes. Physical vapour deposition and chemical vapour deposition can be used to deposit lithiated films. However, the issue of conformality on non-planar substrates with large surface area makes them impractical for nanobatteries the capacity of which scales with surface area. Atomic layer deposition (ALD) avoids these issues and is able to deposit conformal films on 3D substrates. However, ALD is limited in the range of chemical reactions, due to the required volatility of the precursors. Moreover, relatively high temperatures are necessary (above 100 degrees C), which can be detrimental to electrode layers and substrates, for example to silicon into which the lithium can easily diffuse. In addition, several highly reactive precursors, such as Grignard reagents or n-butyllithium (BuLi) are only usable in solution. In theory, it is possible to use BuLi and water in solution to produce thin films of LiH. This theoretical reaction is self-saturating and, therefore, follows the principles of solution atomic layer deposition (sALD). Therefore, in this work the sALD technique and principles have been employed to experimentally prove the possibility of LiH deposition. The formation of homogeneous air-sensitive thin films, characterized by using ellipsometry, grazing incidence X-ray diffraction (GIXRD), in situ quartz crystal microbalance, and scanning electron microscopy, was observed. Lithium hydride diffraction peaks have been observed in as-deposited films by GIXRD. X-ray photoelectron spectroscopy and Auger spectroscopy analysis show the chemical identity of the decomposing air-sensitive films. Despite the air sensitivity of BuLi and LiH, making many standard measurements difficult, this work establishes the use of sALD to deposit LiH, a material inaccessible to conventional ALD, from precursors and at temperatures not suitable for conventional ALD.
CRIS-Team WoS Importer:2019-08-06